In-Depth Analysis of Diet Diary and Urine pH Measurements Improved Food Diet Reporting in Postmenopausal Women with RUTI - Juliann W. Chavez; Alana L. Christie; Philippe E. Zimmern (Mary Ann Liebert, 2024)
Introduction: We proceeded with an in-depth review of diet diaries for nutrient analysis from a cohort of women suffering from uncomplicated recurrent urinary tract infection (RUTI) to validate the accuracy of our current food diet record (FDR) form and evaluate possible domains of improvement. Materials and Methods: As part of an IRB-approved study, this previously published cohort of NHANES-comparable women was analyzed for consistency of the nutrient intake over 3 days, the influence of the time between meals and urine pH, the effect of nutrient intake over interval time between meals, and seasonal and before/during the COVID-19 pandemic changes. Intrarater reliability for nutrient analysis and intrapatient variability for urine pH were computed to test for consistency. Results: Intrarater reliability for diet analysis was 91% accurate for foods and beverage matching and nutrient analysis. Mean standard deviation of urine pH readings within study participants was 0.4 (95% CI: 0.4, 0.5). An association was noted between total calories and fat consumed at breakfast and an increase in time to lunch. Calories consumed were unaffected across seasons or during the COVID-19 pandemic. Water intake during summer was significantly lower than that during fall and winter (both, p < 0.001). The patients who reported drinking water had a significantly lower average urine pH than women who did not report drinking water (5.8 vs. 6.2; p = 0.026). Conclusion: In this cohort of postmenopausal women with RUTIs, in-depth analysis of our current FDR findings led to several actionable items, which will improve our current food diet self-reporting process by our patients.